Interventions for preventing type 2 diabetes in adults with mental disorders in low and middle income countries - Mishu, Masuma Pervin (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of pharmacological, behaviour change, and organisational interventions compared to comparator intervention in preventing diabetes among people with mental illness in LMICs.